2021
DOI: 10.1007/s10956-021-09939-8
|View full text |Cite
|
Sign up to set email alerts
|

Does Learning from Giving Feedback Depend on the Product Being Reviewed: Concept Maps or Answers to Test Questions?

Abstract: Giving feedback to peers can be a valuable learning experience for a feedback provider. However, different types of products require different types of feedback, which, in turn, may lead to different learning outcomes. The current study investigates the effect on the learning of feedback providers of reviewing different types of products. Secondary school students (n =127) were randomly assigned to one of the two conditions: giving peer feedback on either concept maps or answers to open-ended test questions. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In agreement with our findings, the contribution of a similar course, which was provided to improve students’ interpersonal skills in parallel to content field has also been found to be effective in a study of Lopes and colleagues ( 2015 ). Dmoshinskaia and colleagues ( 2022 ) reported that students were interested in a course content although most of it was presented by the students themselves. They felt it was effective, emphasizing the importance of their active participation and feedback providing.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our findings, the contribution of a similar course, which was provided to improve students’ interpersonal skills in parallel to content field has also been found to be effective in a study of Lopes and colleagues ( 2015 ). Dmoshinskaia and colleagues ( 2022 ) reported that students were interested in a course content although most of it was presented by the students themselves. They felt it was effective, emphasizing the importance of their active participation and feedback providing.…”
Section: Discussionmentioning
confidence: 99%